KAJIAN PENGGUNAAN HIGH FRUCTOSE SYRUP (HFS) SEBAGAI PENGGANTI GULA SUKROSA TERHADAP KARAKTERISTIK FISIK DAN KIMIA BISKUIT BERBASIS TEPUNG JAGUNG (Zea mays) DAN TEPUNG KACANG MERAH (Phaseolus vulgaris L.) - Qonitah, Salma Hanin; Affandi, Dian Rachmawanti; Basito, Basito (Jurnal Teknologi Hasil Pertanian, 2016)
The aim of this study were to determine the best formula of HFS biscuit made from corn flour and kidneybean flour based on the sensory characteristics; physical and chemical characteristics of the formulation HFSbiscuit based on corn flour and kidney bean flour based the best biscuit by organoleptic test and compared withIndonesian biscuit’s standard in 2011. The experimental design in this study was completely randomized design(CRD) with one factor which was the concentration of high fructose syrup with 3 weight variations that F1 (19grams), F2 (28.5 grams), and F3 (38 grams). The result of sensory analysis showed that F2 biscuit (28.5 gramsHFS) was the best biscuit. HFS biscuit had 3.85% moisture content, 2.06% ash content, 26.41% fat content,7.89% protein content, and 59.72% carbohydrate content. Calories values of biscuit was 571.91 kcal/100 gramshigher than wheat biscuit. HFS biscuit had maximum force 14.66 N, swelling ratio 16.48% and lighter colorthan control biscuit which had 71.68° Hue. HFS biscuit had qualified to Indonesian biscuit’s standard in 2011(SNI 2973:2011).